Cognitive effects of grammatical gender in L2 acquisition of Spanish: Replicability and reliability of object categorization - Locklear Hannah Webber; Parker Jeff (Open Linguistics)
This study explores the cognitive effects of L2 Spanish acquisition on L2 speakers’ categorization of nouns. We compared monolingual English speakers, L2 Spanish speakers who learned Spanish abroad, and L2 Spanish speakers who learned Spanish in the United States in a task where they assigned adjectives that are stereotypically associated with males or females to nouns of different types. We find effects for both group and noun type; however, contrary to expectations, monolingual English speaker responses were statistically more likely to exhibit a gender-congruence effect than L2 Spanish speaker responses in two groups of nouns, and there was no difference in gender-congruence between the responses of the two L2 Spanish groups. Our results suggest that a speaker’s linguistic knowledge of a language with grammatical gender can affect how they categorize nouns in their native language, but that the direction and strength of the effect may differ across groups and tasks. These results contribute to the ongoing discussion on linguistic relativity and the extent to which one’s linguistic experience influences their perception of the world, including whether learning a second language always increases gendered effects and to what extent such effects are reliable across experimental tasks.